ANALISIS PERBANDINGAN PENDAPATAN ASLI DAERAH DANA ALOKASI UMUM DANA ALOKASI KHUSUS SEBELUM DAN PADA SAAT PANDEMI COVID-19 DI PROVINSI SUMATERA SELATAN - Melia Dwi Khairunisa; Nelly Maslina; Darul Amri (Gapenas Publisher, 2023)
Covid-19 is a disease that until now still affects the world community, especially Indonesian citizens.The spread of the Covid-19 virus in Indonesia until now continues to spread widely, not only spread in urban areas, this spread extends to rural areas resulting in thousands or even hundreds of thousands of people dying due to corona virus infection. Such as in Sumatra, especially South Sumatra Province. Since April 2020, several regions in South Sumatra have been included in the red zone, including the cities of Palembang, Prabumulih, Lubuk Linggau, Ogan Komering Ulu (OKU) and Banyuasin. This is due to the rapid transmission of the Covid-19 virus which resulted in South Sumatra being ranked 7th in the highest confirmed cases in Indonesia. In this sampling. Researchers use sampling technique method, namely Non probability sampling using saturated sampling. The sample in this study was all members of the population of 17 provincial districts in South Sumatra. The data used uses secondary data in the form of audited Financial Statements. The analysis tool in this study used the Difference Test. The results showed that there were significant differences in the General Allocation Fund (DAU) and Special Allocation Fund (DAK) before and during the COVID19 pandemic, while in Regional Original Revenue (PAD) there was no significant difference before and during the COVID-19 pandemic in South Sumatra Province